Pelatihan Pertolongan Pertama Bagi Nelayan di Pantai Kondang Merak, Kabupaten Malang - Setyawan, Fahreza Okta; Aliviyanti, Dian; Yamindago, Ade; Yona, Defri; Fuad, Muhammad Arif Zainul; Isdianto, Andik; Rijal, Seftiawan Samsu; Guntur (Abdi Geomedisains, 2024)
Kondang Merak Beach has several community groups that inhabit and manage the beach. One of the local community groups is Bina Karya Mina fishing group. Apart from fishing, which was their main livelihood, this group of fishermen was also proficient in diving and snorkeling. However, due to the lack of training in diving for the fishermen, the diving equipment that is there is not properly utilized. Knowledge about first aid for diving accident victims is also needed not only when a fishermen’s diving accident occurs but can also be used to help tourists when an accident occurs while snorkeling or swimming at the beach. This community service activity aimed to increase the knowledge and skills of the Bina Karya Mina fishing group in terms of diving, especially first aid for accident victims at Kondang Merak Beach, Malang Regency. This activity was divided into three stages of activity, namely the preparation, implementation, evaluation, and reporting stages. The implementation stage of this community service activity was carried out in a hybrid manner, namely socialization material was given online, while practical activities and handover of first aid assistance are carried out offline. Through this activity, it was expected to improve the ability of fishermen in the field of diving. In addition, socialization about first aid kits as supporting equipment to help accident victims was carried out as well so that they could increase the preparedness of fishermen on Kondang Merak Beach in case of an emergency.